Endogenous Altruism: Theory and Evidence from Chinese Twins - Yi, Junjian (Journal of Labor Economics, 2019)
This paper studies the endogenous formation of intersibling altruism. The theory suggests that parental incentive to foster children’s fraternal love is positively related to efficiency gains from more human capital investment in the more gifted child. The empirical analyses explore the plausibly exogenous within-twin difference in birth weight, a proxy for prenatal endowment. Consistent with the theory, the estimation results show that a larger difference in children’s birth weight leads to more intensive parenting practice to foster children’s fraternal love and that when such practice is more intensive, the heavier child obtains more investment relative to the other child.